VIABILITAS PSEUDOMONAD Fluorescens ISOLAT Pf-122 DALAM BEBERAPA FORMULA - Yenny Wuryandari; Arika Purnawati; Siswanto Siswanto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
The objectives of this research were to examine effect of several formulas on the viability of Pseudomonas Fluorescens isolate Pf- 122. The eight formulations include carriers, additives, and concentration of Pf-122. The efficacy of various formulation in maintaining the population of Pf-122 in storage was assessed. The result of the viability test of Pf-122 in formula showed that the highest population of Pf-122 in week 0 was observed on the formula 1, viz the formula with combination of pupuk kandang as carrier and CMC as additive and Pf-122 at the concentration of 1010 CFU/ml. The bacterial population of the formula number1 could reach 4.8 × 1010 CFU/formula and followed by the formulas number 2,3,4,5,6, and 7. The lowest population was observed on the formula number 8 with the density of 5.8 × 106 CFU/formula. The bacterial population decreased during storage in all of the formulas and even it could not be detectedin the formulas number 3 and 4 after the first week of storage. In the formulas number 1 and 2 survived within 3 months.